PENGARUH PENERAPAN SISTEM AKUNTANSI PEMERINTAH DAERAH, PEMAHAMAN AKUNTANSI, DAN KETAATAN PADA PERATURAN PERUNDANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi Pada Satuan Kerja Perangkat Daerah Kota Pekanbaru) - Khodri Zulharman; Zulbahridar -; Hariadi - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of implementation local government accounting system, the understanding of accounting, and the adherence of the law regulation on the performance accountability of goverment institution. Population and sample in this study was SKPD the city of Pekanbaru. Collecting data using primary data collection, the questionnaires by using sensus technique. This study used multiple linier regression analysis techniques. The results of this study were : 1). Implementation of local government accounting system positive effect on the performance accountability goverment institution. 2). Understanding of accounting has a positive effect on the performance accountability goverment institution. 3). The adherence of the law regulation positive effect on the performance accountability goverment institution.Keywords: performance accountability, accounting system, the adherence, and the law regulation.